ANALISIS MULTIMODAL DALAM TEKS IKLAN DALAM PERSPEKTIF SEMIOTIK - Zainuddin Zainuddin (BAHAS, 2017)
The study describes an analysis of multimodal in terms of semiotics in the text of advertisement. It is to find out the meanings of verbal and visual components in the text of advertisement. In other words, the analysis deals with two different aspects namely  verbal and visual meanings. The source of the data advertisement text  taken from brochure Honda BR-V dalam bentuk gambar visual. The analysis of multimodal in the text of advertisement applied the theory of Halliday (1994) and Cheong (2004). The findings indicating that verbal component consists of some components namely announcement: primary, secondary; enhancer; emblem; tag and call-and-visit information. And visual components comprising of some components they are Lead: Locus of Attention (LoA), Complement to the Locus of Attention (Comp. LoA), Display: Explicit, Implicit, Congruent, Incongruent (metaphorical), and Emblem.